Forward osmosis membrane for seawater electrolysis hydrogen production and preparation method thereof
By adopting a double-layer structure of base membrane and composite layer in the forward osmosis membrane, and utilizing the chemical grafting reaction of aromatic hydrocarbon-substituted hydrophilic silicone groups and active groups, the existing forward osmosis membrane solves the problem of seawater electrolysis in hydrogen production. It solves the problem of insufficient alkali resistance, achieves efficient water molecule transmission and ion blocking, improves electrolysis efficiency and reduces seawater pollution.
Patent Information
- Application Number
- CN202310882125.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing positive permeability membranes have problems such as insufficient alkali resistance, ion diffusion and electrode corrosion during the direct electrolysis of seawater hydrogen production, resulting in low electrolytic efficiency and seawater pollution.
The bilateral structure of the base film and the composite layer reacts with hydrophilic organic silicon -based silicon -based silicon -based silicon -based silicon -based and chemical branches of the alcoholic group, forming a positive permeability membrane with alkali resistance and heat resistance.
The excellent alkali resistance, heat resistance, and high water flux of the positive permeability membrane can effectively prevent the migration of impurities ions, improve the electrolytic efficiency and reduce seawater pollution.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of membrane separation technology, and in particular, to a forward osmosis membrane for hydrogen production by seawater electrolysis and a preparation method thereof. Background Art
[0002] Forward osmosis technology uses the osmotic pressure difference of the solution on both sides of the semipermeable membrane under normal pressure conditions to achieve spontaneous separation of the solution, and has shown great potential in the production of hydrogen by electrolysis of seawater. However, in the process of direct electrolysis of seawater to produce hydrogen, since the forward osmosis membrane needs to be in contact with the electrolyte solution at all times, and ordinary commercial forward osmosis membranes cannot withstand strong alkalinity for a long time, only neutral electrolytes can be used in the process of electrolysis of water to produce hydrogen, resulting in low electrolysis efficiency. At the same time, the ion diffusion of ordinary commercial forward osmosis membranes causes corrosion to the electrodes, shortening the service life of the electrodes, and the ions in the electrolyte leak into the seawater, causing seawater pollution problems.
[0003] At present, the most widely used and efficient method for preparing forward osmosis membranes is to prepare composite forward osmosis membranes by interfacial polymerization. This method usually involves in-situ growth of an ultra-thin aromatic polymer as a separation layer on a polysulfone support layer. Although this technology is mature, composite forward osmosis membranes still have disadvantages such as low hydrophilicity, poor resistance to strong alkali, and ion diffusion, making them unsuitable for direct application in direct hydrogen production by seawater electrolysis.
[0004] Prior art (CN109304088A) discloses a strong acid and alkali resistant seawater desalination membrane and its preparation method and application, which mainly mixes graphene with strong acid and alkali resistance with water-soluble natural polymer materials, and cross-links and coats it on the surface of the base film to obtain a strong acid and alkali resistant seawater desalination membrane. However, in this technical solution, it is necessary to first ultrasonically disperse the graphene to obtain a homogeneous mixed solution. The dispersion time required for this step is relatively long, requiring 40-60 minutes, and in the process of large-scale preparation, graphene is easily dispersed unevenly, which may cause the performance of the seawater desalination membrane to be affected; in addition, the high price of graphene will greatly increase the preparation cost of the seawater desalination membrane, which is not conducive to large-scale production and application. Therefore, a new forward osmosis membrane suitable for the direct electrolysis of seawater to produce hydrogen is urgently needed. Summary of the invention
[0005] The purpose of the present disclosure is to provide a forward osmosis membrane for hydrogen production by seawater electrolysis and a preparation method thereof, wherein the forward osmosis membrane has excellent alkali resistance, heat resistance and rigidity, and has a large water flux and can effectively prevent the diffusion of ions.
[0006] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a forward osmosis membrane for producing hydrogen by electrolysis of seawater, the forward osmosis membrane comprising a base membrane and a composite layer covering the surface of the base membrane;
[0007] The composite layer contains hydrophilic organosilicon groups substituted with aromatic hydrocarbon groups; the surface of the base film contains active groups, which include one or more of carboxyl groups, amine groups, hydroxyl groups, acetate groups, amide groups, amino groups, aldehyde groups and carbonyl groups;
[0008] The base film and the composite layer are connected through a chemical grafting reaction between the hydrophilic organic silicon group substituted by the aromatic hydrocarbon group and the active group.
[0009] Optionally, the aromatic hydrocarbon group is selected from aromatic hydrocarbon groups having 6 to 12 carbon atoms; the hydrophilic silicone group is selected from one or more of an active polyether silicone group, a polydimethylsiloxane group, a polymethyl hydrogen-(dimethyl)siloxane group, a terminal hydroxyl polydimethylsiloxane group and an aminoethylaminopropyl polysiloxane group;
[0010] Preferably, the aromatic hydrocarbon group is selected from one or more of o-xylyl, m-xylyl, p-xylyl, 1,3,5-triaminophenyl, 1,2,4-triaminophenyl and 2,4-diaminotolyl.
[0011] Optionally, the base film is selected from cellulose acetate film and / or polyamide film; the thickness of the base film is 0.01-0.1 mm.
[0012] Optionally, the forward osmosis membrane has a tolerance pH of 1-14, a water migration rate of 0.01-0.5 gH2O / g KOH / min, a contact angle of 5-60° with water, a permeability of impurity ions within 72 hours of the forward osmosis membrane of 0.005-0.08‰, and a temperature tolerance of 20-70°C.
[0013] A second aspect of the present disclosure provides a method for preparing a forward osmosis membrane for hydrogen production by seawater electrolysis, the method comprising the following steps:
[0014] S1, contacting the basement membrane with an activation solution for activation treatment to obtain an activated basement membrane; the activated basement membrane contains active groups, and the active groups include one or more of carboxyl, amine, hydroxyl, acetate, amide, amino, aldehyde and carbonyl groups;
[0015] S2, contacting the activated base membrane with a modification solution for modification treatment, drying the obtained modified base membrane to obtain the forward osmosis membrane; the modification solution contains hydrophilic silicone substituted with aromatic hydrocarbon groups.
[0016] Optionally, in step S1, the activation treatment conditions include: temperature of 20-30°C, time of 0.5-2h; the activation solution contains hydrogen peroxide and / or sodium hypochlorite, the concentration of the activation solution is 50-500ppm, and the pH value is 7-11.
[0017] Optionally, in step S2, the modification treatment conditions include: temperature of 25-35°C, time of 1-3h; the drying conditions include: temperature of 70-80°C, time of 0.5-2h.
[0018] Optionally, in step S2, the hydrophilic organosilicon and the aromatic hydrocarbon solvent are mixed to obtain the modified solution, and the amount of the hydrophilic organosilicon is 0.5-3% by weight based on the total weight of the hydrophilic organosilicon and the aromatic hydrocarbon solvent.
[0019] Optionally, the aromatic hydrocarbon solvent contains aromatic hydrocarbons with 6-12 carbon atoms; the hydrophilic silicone is selected from one or more of active polyether silicone, polydimethylsiloxane, polymethyl hydrogen-(dimethyl)siloxane, terminal hydroxyl polydimethylsiloxane and aminoethyl iminopropyl polysiloxane;
[0020] Preferably, the aromatic hydrocarbon solvent contains one or more of o-xylene, m-xylene, p-xylene, 1,3,5-triaminobenzene, 1,2,4-triaminobenzene and 2,4-diaminotoluene.
[0021] Optionally, the base film is selected from cellulose acetate film and / or polyamide film; the thickness of the base film is 0.01-0.1 mm.
[0022] Through the above technical solution, the present disclosure provides a forward osmosis membrane for hydrogen production by seawater electrolysis and a preparation method thereof, which has the following advantages:
[0023] (1) The forward osmosis membrane disclosed in the present invention has a double-layer structure of a base membrane and a composite layer, and the base membrane and the composite layer are connected by a chemical grafting reaction between a hydrophilic organosilicon group substituted with an aromatic hydrocarbon group and an active group. Among them, the use of hydrophilic organosilicon to modify the membrane surface can further improve the hydrophilicity and alkali resistance of the forward osmosis membrane surface, and the dual properties of inorganic and organic substances of organosilicon make the impurity ion migration of the forward osmosis membrane disclosed in the present invention less.
[0024] (2) The present invention adopts a surface modification method to modify the surface of the forward osmosis membrane, which has a simple process, low cost, and is easy to mass produce. The prepared forward osmosis membrane has high stability, excellent alkali resistance and hydrophilicity, and less migration of impurity ions.
[0025] Other features and advantages of the present disclosure will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0026] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0027] In a first aspect, the present disclosure provides a forward osmosis membrane for hydrogen production by electrolysis of seawater, the forward osmosis membrane comprising a base membrane and a composite layer covering the surface of the base membrane; the composite layer contains a hydrophilic organosilicon group substituted with an aromatic hydrocarbon group; the surface of the base membrane contains active groups, the active groups comprising one or more of a carboxyl group, an amine group, a hydroxyl group, an acetate group, an amide group, an amino group, an aldehyde group and a carbonyl group; the base membrane and the composite layer are connected by a chemical grafting reaction between the hydrophilic organosilicon group substituted with an aromatic hydrocarbon group and the active group.
[0028] The forward osmosis membrane disclosed in the present invention has a double-layer structure of a base membrane and a composite layer covering the surface of the base membrane. The hydrophilic silicone group substituted by an aromatic hydrocarbon group is connected to the active group on the surface of the base membrane through a chemical grafting reaction, so that the forward osmosis membrane disclosed in the present invention has excellent alkali resistance, heat resistance, rigidity, and a large water flux and can effectively prevent the migration of impurity ions. Among them, the aromatic hydrocarbon group can improve the heat resistance and rigidity of the forward osmosis membrane; the bond energy of the silicon oxygen bond in the hydrophilic silicone group is large, so that the forward osmosis membrane has excellent alkali resistance, the silicon atom has a large volume and a large free volume in the spatial structure, which can make the forward osmosis membrane have a large water flux; in addition, the main chain of the hydrophilic silicone is an inorganic structure containing a silicon oxygen bond, and the side chain part is mainly an organic group, so it has the dual properties of inorganic and organic substances at the same time, so that the forward osmosis membrane disclosed in the present invention can effectively prevent the diffusion and migration of ions.
[0029] In a specific embodiment of the present disclosure, the composite layer is covered on at least one main surface of the base film. Preferably, the composite layer includes a first composite layer and a second composite layer. The first composite layer is covered on the first main surface of the base film, and the second composite layer is covered on the second main surface of the base film. The first main surface and the second main surface refer to two opposite surfaces in the thickness direction of the base film.
[0030] In the present disclosure, the number of carbon atoms of the aromatic hydrocarbon group can vary within a wide range. In one embodiment of the present disclosure, the aromatic hydrocarbon group is selected from aromatic hydrocarbon groups with 6-12 carbon atoms, preferably selected from aromatic hydrocarbon groups with 6-9 carbon atoms; the hydrophilic silicone group is well known to those skilled in the art, preferably selected from one or more of an active polyether silicone group, a polydimethylsiloxane group, a polymethyl hydrogen-(dimethyl)siloxane group, a terminal hydroxyl polydimethylsiloxane group and an aminoethyl iminopropyl polysiloxane group; in a preferred embodiment of the present disclosure, the aromatic hydrocarbon group is selected from one or more of o-xylyl, m-xylyl, p-xylyl, 1,3,5-triaminophenyl, 1,2,4-triaminophenyl and 2,4-diaminotolyl.
[0031] In one embodiment of the present disclosure, the base film is selected from cellulose acetate film and / or polyamide film. In the above embodiment, after the base film is activated, the chemical bonds on the surface of the base film are broken to form active groups, for example, one or more of carboxyl groups, amine groups, hydroxyl groups and acetate groups. The base film can also be a composite film, which is made of two or more materials. The composite film includes a separation layer and a porous support layer. The material of the separation layer is selected from one or more of aromatic polyamide, piperazineamide, propylene-alkyl polyamide, condensed urea, furfuryl alcohol, trihydroxyethyl isocyanate and metaphenylenediamine, and the material of the porous support layer is one or more of non-woven fabrics, polysulfone, polypropylene and polyacrylonitrile.
[0032] In the present disclosure, the thickness of the base membrane can vary within a wide range. In one embodiment of the present disclosure, the thickness of the base membrane can be 0.01-0.1 mm, preferably 0.01-0.05 mm; when the thickness of the base membrane is within the range of the present disclosure, the performance of the modified forward osmosis membrane can be further improved.
[0033] In the present disclosure, the tolerable pH value, water migration rate, contact angle with water, permeability of impurity ions within 72 hours and tolerable temperature of the forward osmosis membrane can vary within a large range. In one embodiment of the present disclosure, the tolerable pH value of the forward osmosis membrane is 1-14, the water migration rate of the forward osmosis membrane is 0.01-0.5g H2O / g KOH / min, the contact angle with water of the forward osmosis membrane is 5-60°, the permeability of impurity ions within 72 hours of the forward osmosis membrane is 0.005-0.08‰, and the tolerable temperature of the forward osmosis membrane is 20-70°C.
[0034] In the present disclosure, the measurement is obtained by the following experimental method: the forward osmosis membrane is soaked in sodium hydroxide / hydrochloric acid solutions with different pH values for 24 hours, and then rinsed with pure water. The water migration rate of the forward osmosis membrane before and after soaking is measured. If the change in the water migration rate of the forward osmosis membrane before and after soaking exceeds 5%, it means that the forward osmosis membrane is intolerant to the pH value. The water migration rate of the forward osmosis membrane is measured by the following experimental method: the water migration rate of the forward osmosis membrane is measured by measuring the weight change of the electrolyte solution at 25°C, and a certain amount of 2mol / L KOH solution and 0.5mol / L NaCl solution are placed on both sides of the forward osmosis membrane. The change in the mass of KOH is recorded at regular intervals to obtain the water migration rate of the forward osmosis membrane. The contact angle with water is detected by a contact angle meter. The permeability of impurity ions within 72 hours is measured by the following experimental method: the impurity ion permeability of the forward osmosis membrane is tested on a laboratory seawater electrolysis hydrogen production device, and the forward osmosis membrane is fixed between the anode and cathode plates, one side is the electrolyte solution, and the other side is seawater, at 400mA / cm 2The test was run continuously for 72 hours at a current density of , and the content of impurity ions in the electrolyte solution was determined. The temperature tolerance of the forward osmosis membrane was measured by the following experimental method: the forward osmosis membrane was immersed in aqueous solutions of different temperatures for 72 hours and then taken out. The water migration rate of the forward osmosis membrane before and after immersion was measured. If the change in the water migration rate of the forward osmosis membrane before and after immersion exceeded 2%, it means that the forward osmosis membrane is intolerant to the temperature.
[0035] A second aspect of the present disclosure provides a method for preparing a forward osmosis membrane for hydrogen production by seawater electrolysis, the method comprising the following steps:
[0036] S1, contacting the basement membrane with an activation solution for activation treatment to obtain an activated basement membrane; the activated basement membrane contains active groups, and the active groups include one or more of carboxyl, amine, hydroxyl, acetate, amide, amino, aldehyde and carbonyl groups;
[0037] S2, contacting the activated base membrane with a modification solution for modification treatment, drying the obtained modified base membrane to obtain the forward osmosis membrane; the modification solution contains hydrophilic silicone substituted with aromatic hydrocarbon groups.
[0038] In the present invention, the surface of the forward osmosis membrane is modified by surface modification. The process for preparing the forward osmosis membrane is simple, low-cost, and easy to mass-produce. The prepared forward osmosis membrane has high stability, excellent alkali resistance and hydrophilicity, and less migration of impurity ions.
[0039] In a specific embodiment of the present disclosure, in step S1, the base film is immersed in an activation solution for activation treatment to obtain an activated base film. Preferably, the activated base film is washed with a solvent to remove the activation solution remaining on the surface of the activated base film. The present disclosure does not specifically limit the type of solvent as long as it does not react with the surface of the activated base film, and can be, for example, deionized water.
[0040] In a specific embodiment of the present disclosure, in step S2, the activated base film is immersed in a modification solution for modification treatment to obtain a modified base film.
[0041] In the present disclosure, the temperature and time of the activation treatment can vary within a wide range. In one embodiment of the present disclosure, in step S1, the conditions of the activation treatment include: a temperature of 20-30°C and a time of 0.5-2h; preferably, a temperature of 25-30°C and a time of 1-1.5h. Controlling the temperature and time of the activation treatment within the range of the above embodiment can further promote the activation of the basement membrane.
[0042] According to the present disclosure, the activation solution contains an oxidant. In one embodiment of the present disclosure, the activation solution contains hydrogen peroxide and / or sodium hypochlorite. In the present disclosure, the concentration and pH value of the activation solution can vary within a wide range. In one embodiment of the present disclosure, the concentration of the activation solution is 50-500ppm, preferably 200-400ppm, and the pH value is 7-11, preferably 7-9. Controlling the concentration and pH value of the activation solution within the range of the above-mentioned embodiment can further promote the breaking of chemical bonds on the surface of the base membrane to form active groups, so as to undergo a chemical grafting reaction with the hydrophilic silicone substituted with aromatic hydrocarbon groups in the modified solution in the subsequent process, thereby preparing a forward osmosis membrane with good stability.
[0043] The present disclosure does not specifically limit the method for adjusting the pH value of the activation solution. In a specific embodiment of the present disclosure, an acid solution is used to adjust the pH value of the activation solution. The acid solution contains hydrogen chloride and / or sodium hydroxide. The concentration of the acid in the acid solution can be selected as needed, for example, it can be 2-4 mol / L.
[0044] In the present disclosure, the temperature and time of the modification treatment can vary within a wide range. In one embodiment of the present disclosure, in step S2, the conditions of the modification treatment include: a temperature of 25-35°C and a time of 1-3h; preferably, a temperature of 28-30°C and a time of 1-2h. The conditions of the modification treatment are more suitable within the above range, which is conducive to the chemical grafting reaction. The temperature and time of the modification treatment can be controlled within the range of the above embodiment, which can further promote the modification of the base film.
[0045] In the present disclosure, drying can be performed in equipment conventionally used by those skilled in the art, such as a constant temperature drying oven, etc. In one embodiment of the present disclosure, the drying conditions include: a temperature of 70-80°C and a time of 0.5-2h; preferably, a temperature of 70-75°C and a time of 1-2h.
[0046] In one embodiment of the present disclosure, in step S2, the hydrophilic organosilicon and the aromatic hydrocarbon solvent are mixed to obtain the modified solution, and the amount of the hydrophilic organosilicon is 0.5-3% by weight, preferably 1-2% by weight, based on the total weight of the hydrophilic organosilicon and the aromatic hydrocarbon solvent. The present disclosure does not specifically limit the time and temperature of mixing, for example, it can be mixed at room temperature for 3-20 minutes, and more preferably mixed and stirred at 30-35°C for 5-10 minutes, so that the hydrophilic organosilicon and the aromatic hydrocarbon solvent undergo a substitution reaction, replacing at least one hydrogen atom on the aromatic hydrocarbon benzene ring to obtain an aromatic hydrocarbon-substituted hydrophilic organosilicon. In the present disclosure, controlling the amount of the hydrophilic organosilicon within the scope of the above embodiment can further promote the modification of the modified solution to the activated base film, which is conducive to the preparation of a forward osmosis membrane with excellent alkali resistance, heat resistance and rigidity, so that the forward osmosis membrane is more conducive to the transmission of water molecules and can prevent the diffusion and migration of ions.
[0047] In one embodiment of the present disclosure, the aromatic hydrocarbon solvent contains aromatic hydrocarbons having 6-12 carbon atoms, preferably aromatic hydrocarbons having 6-9 carbon atoms; the hydrophilic silicone is well known to those skilled in the art, preferably one or more selected from active polyether silicone, polydimethylsiloxane, polymethyl hydrogen-(dimethyl)siloxane, terminal hydroxyl polydimethylsiloxane and aminoethyliminopropylpolysiloxane; preferably, the aromatic hydrocarbon solvent contains one or more of o-xylene, m-xylene, p-xylene, 1,3,5-triaminobenzene, 1,2,4-triaminobenzene and 2,4-diaminotoluene.
[0048] In one embodiment of the present disclosure, the base film is selected from cellulose acetate film and / or polyamide film; the thickness of the base film is 0.01-0.1 mm, preferably 0.01-0.05 mm.
[0049] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.
[0050] Unless otherwise specified, the materials used in this example and comparative example are all commercially available products.
[0051] Example 1
[0052] (1) Preparation of activation solution: Prepare 500 ppm sodium hypochlorite solution, and adjust the pH value of the sodium hypochlorite solution to 11 using a 3 mol / L dilute hydrochloric acid solution to obtain an activation solution.
[0053] (2) Activation of base film: A cellulose acetate film having a thickness of 0.03 mm was immersed in the activation solution prepared in step (1) at 28° C. for 1 h to obtain an activated cellulose acetate film.
[0054] (3) Preparation of modified solution: Add active polyether silicone to o-xylene, stir at 32° C. for 5 min, and use 1 wt % of hydrophilic silicone based on the total weight of the hydrophilic silicone and o-xylene.
[0055] (4) The activated cellulose acetate membrane was immersed in the modified solution prepared in step (3) at 30° C. for 2 h, and then the modified cellulose acetate membrane was dried at 70° C. for 2 h to obtain a forward osmosis membrane A.
[0056] Example 2
[0057] (1) Preparation of activation solution: Prepare 200 ppm hydrogen peroxide solution, and use 2 mol / L sodium hydroxide solution to adjust the pH value of the hydrogen peroxide solution to 11.
[0058] (2) Activation of base film: a polyamide film with a thickness of 0.04 mm was immersed in the activation solution prepared in step (1) at 25° C. for 1.5 h to obtain an activated polyamide film.
[0059] (3) Preparation of modified solution: Add polymethyl hydrogen-(dimethyl)siloxane to m-xylene and stir at 30° C. for 5 min. The amount of hydrophilic silicone is 2 wt % based on the total weight of the hydrophilic silicone group and m-xylene.
[0060] (4) The activated polyamide membrane was immersed in the modified solution prepared in step (3) at 25° C. for 3 h, and then the modified polyamide membrane was dried at 70° C. for 1.5 h. A forward osmosis membrane B was obtained.
[0061] Example 3
[0062] A forward osmosis membrane was prepared by the same method as in Example 1, except that the base membrane was a polyamide membrane with a thickness of 0.04 mm, the organosilicon was polydimethylsiloxane, and the aromatic hydrocarbon solvent was m-xylene. A forward osmosis membrane C was obtained.
[0063] Example 4
[0064] A forward osmosis membrane was prepared by the same method as in Example 1, except that the base membrane was a composite membrane with a thickness of 0.05 mm, the organosilicon was hydroxy-terminated polydimethylsiloxane, and the aromatic hydrocarbon solvent was 1,2,4-triaminophenyl. A forward osmosis membrane D was obtained.
[0065] Example 5
[0066] A forward osmosis membrane was prepared by the same method as in Example 1, except that in step (4), the activated cellulose acetate membrane was immersed in the modified solution prepared in step (3) for 0.5 h at 20° C., and then the modified cellulose acetate membrane was dried at 70° C. for 0.5 h. A forward osmosis membrane E was obtained.
[0067] Example 6
[0068] A forward osmosis membrane was prepared by the same method as in Example 1, except that, in step (1), a 500 ppm sodium hypochlorite solution was prepared, and the pH value of the sodium hypochlorite solution was adjusted to 11 using a 3 mol / L dilute hydrochloric acid solution to obtain an activation solution;
[0069] In step (2), a cellulose acetate membrane having a thickness of 0.03 mm is immersed in the activation solution prepared in step (1) at 35° C. for 3 h to obtain an activated cellulose acetate membrane. A forward osmosis membrane F is obtained.
[0070] Test Example 1
[0071] This test example is used to illustrate the pH tolerance of the forward osmosis membrane.
[0072] The forward osmosis membranes A, B, C, D, E, F obtained in Examples 1-6, as well as the unmodified cellulose acetate membrane and the unmodified polyamide membrane were subjected to a pH tolerance test; the membranes were immersed in sodium hydroxide / hydrochloric acid solutions with different pH values for 24 hours, and then rinsed with pure water. The water migration rate of the membranes before and after immersion was measured. If the change in the water migration rate before and after immersion exceeded 5%, it means that the membrane is intolerant to the pH value.
[0073] The results are listed in Table 1.
[0074] Test Example 2
[0075] This test example is used to illustrate the water migration rate of the forward osmosis membrane.
[0076] The forward osmosis membranes A, B, C, D, E, F obtained in Examples 1-6, as well as the unmodified cellulose acetate membrane and the unmodified polyamide membrane were subjected to water migration rate determination; the water migration rate of the membrane was determined by measuring the weight change of the electrolyte solution at 25°C. A certain amount of 2 mol / L KOH solution and 0.5 mol / L NaCl solution were placed on both sides of the membrane, respectively, and the change in the mass of KOH was recorded at regular intervals, and the water migration rate of the membrane could be obtained.
[0077] The results are listed in Table 1.
[0078] Test Example 3
[0079] This test example is used to illustrate the contact angle of water on the forward osmosis membrane.
[0080] The forward osmosis membranes A, B, C, D, E, F, unmodified cellulose acetate membranes and unmodified polyamide membranes obtained in Examples 1-6 were subjected to water contact angle measurement; the contact angles of the membranes were measured using a contact angle meter.
[0081] The results are listed in Table 1.
[0082] Test Example 4
[0083] This test example is used to illustrate the permeability of impurity ions within 72 hours of the forward osmosis membrane.
[0084] The forward osmosis membranes A, B, C, D, E, F obtained in Examples 1-6, as well as the unmodified cellulose acetate membrane and the unmodified polyamide membrane were tested for the permeability of impurity ions in water. The permeability of impurity ions in the membrane was tested on a laboratory seawater electrolysis hydrogen production device. The membrane was fixed between the anode and cathode plates, with the electrolyte solution on one side and seawater on the other side. The permeability of impurity ions in water was tested at 400 mA / cm 2 The test was run continuously for 72 h at a current density of , and the content of impurity ions in the electrolyte solution was determined.
[0085] The results are listed in Table 1.
[0086] Test Example 5
[0087] This test example is used to illustrate the heat resistance of the forward osmosis membrane.
[0088] The forward osmosis membranes A, B, C, D, E, F obtained in Examples 1-6, as well as the unmodified cellulose acetate membrane and the unmodified polyamide membrane were tested for heat resistance; the membranes were immersed in aqueous solutions at different temperatures for 72 hours and then taken out. The water migration rate of the membranes before and after immersion was measured. If the change in the water migration rate before and after immersion exceeded 2%, it means that the membrane cannot tolerate the temperature value.
[0089] The results are listed in Table 1.
[0090] Test Example 6
[0091] This test example is used to illustrate the tensile strength of the forward osmosis membrane.
[0092] The forward osmosis membranes A, B, C, D, E, F obtained in Examples 1-6, as well as the unmodified cellulose acetate membrane and the unmodified polyamide membrane were tested for tensile strength; the tensile strength was tested using a film tensile testing machine.
[0093] The results are listed in Table 1.
[0094] Table 1
[0095]
[0096]
[0097] From the data in Table 1, it can be seen that compared with the unmodified cellulose acetate membrane and the unmodified polyamide membrane, the forward osmosis membranes prepared in Examples 1-6 have higher pH tolerance, water migration rate, heat resistance and tensile strength than the unmodified cellulose acetate membrane and the unmodified polyamide membrane, and the contact angle transmittance of impurity ions and water within 72 hours is less than that of the unmodified cellulose acetate membrane and / or the unmodified polyamide membrane. It is proved that the forward osmosis membrane prepared by the method of the present disclosure has excellent alkali resistance, heat resistance and rigidity, and has a large water flux and can effectively prevent the diffusion of ions.
[0098] In Examples 1-6:
[0099] Compared with Example 5, the modification treatment conditions of Example 5 are not within the scope of the present disclosure. The pH tolerance, water migration rate, heat resistance and tensile strength of the forward osmosis membrane prepared in Example 1 are higher than those of the forward osmosis membrane prepared in Example 5, and the contact angle transmittance of impurity ions and water within 72 hours is lower than that of the osmosis membrane prepared in Example 5, indicating that controlling the modification treatment conditions within the scope of the present disclosure is beneficial to improving the performance of the forward osmosis membrane.
[0100] Compared with Example 6, the activation treatment conditions of Example 6 are not within the scope of the present disclosure. The pH tolerance, water migration rate, heat resistance and tensile strength of the forward osmosis membrane prepared in Example 1 are higher than those of the forward osmosis membrane prepared in Example 6, and the contact angle transmittance of impurity ions and water within 72 hours is lower than that of the osmosis membrane prepared in Example 6, indicating that controlling the activation treatment conditions within the scope of the present disclosure is beneficial to improving the performance of the forward osmosis membrane.
[0101] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0102] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0103] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A forward osmosis membrane for hydrogen production by seawater electrolysis, characterized in that: The forward osmosis membrane comprises a base membrane and a composite layer covering the surface of the base membrane; The composite layer contains hydrophilic organosilicon groups substituted with aromatic hydrocarbon groups; the surface of the base film contains active groups, which include one or more of carboxyl groups, amine groups, hydroxyl groups, acetate groups, amide groups, amino groups, aldehyde groups and carbonyl groups; The base film and the composite layer are connected through a chemical grafting reaction between the hydrophilic organic silicon group substituted by an aromatic hydrocarbon group and the active group.
2. The forward osmosis membrane according to claim 1, characterized in that The aromatic hydrocarbon group is selected from aromatic hydrocarbon groups having 6 to 12 carbon atoms; the hydrophilic silicone group is selected from one or more of an active polyether silicone group, a polydimethylsiloxane group, a polymethyl hydrogen-(dimethyl)siloxane group, a terminal hydroxyl polydimethylsiloxane group and an aminoethyliminopropyl polysiloxane group; Preferably, the aromatic hydrocarbon group is selected from one or more of o-xylyl, m-xylyl, p-xylyl, 1,3,5-triaminophenyl, 1,2,4-triaminophenyl and 2,4-diaminotolyl.
3. The forward osmosis membrane according to claim 1, characterized in that The base film is selected from cellulose acetate film and / or polyamide film; the thickness of the base film is 0.01-0.1 mm.
4. The forward osmosis membrane according to claim 1, characterized in that The forward osmosis membrane has a tolerable pH value of 1-14, a water migration rate of 0.01-0.5 g H2O / g KOH / min, a contact angle of 5-60° with water, a permeability of impurity ions within 72 hours of the forward osmosis membrane of 0.005-0.08‰, and a tolerable temperature of 20-70°C.
5. A method for preparing a forward osmosis membrane for hydrogen production by seawater electrolysis, characterized in that: The method comprises the following steps: S1, contacting the basement membrane with an activation solution for activation treatment to obtain an activated basement membrane; the activated basement membrane contains active groups, and the active groups include one or more of carboxyl, amine, hydroxyl, acetate, amide, amino, aldehyde and carbonyl groups; S2, contacting the activated base membrane with a modification solution for modification treatment, drying the obtained modified base membrane to obtain the forward osmosis membrane; the modification solution contains hydrophilic silicone substituted with aromatic hydrocarbon groups.
6. The preparation method according to claim 5, characterized in that: In step S1, the activation treatment conditions include: temperature of 20-30°C and time of 0.5-2h; The activation solution contains hydrogen peroxide and / or sodium hypochlorite, the concentration of the activation solution is 50-500 ppm, and the pH value is 7-11.
7. The preparation method according to claim 5, characterized in that: In step S2, the modification treatment conditions include: temperature of 25-35°C, time of 1-3h; the drying conditions include: temperature of 70-80°C, time of 0.5-2h.
8. The preparation method according to claim 5, characterized in that: In step S2, the hydrophilic organosilicon and the aromatic hydrocarbon solvent are mixed to obtain the modified solution, and the amount of the hydrophilic organosilicon is 0.5-3% by weight based on the total weight of the hydrophilic organosilicon and the aromatic hydrocarbon solvent.
9. The preparation method according to claim 8, characterized in that: The aromatic hydrocarbon solvent is an aromatic hydrocarbon having 6 to 12 carbon atoms; the hydrophilic silicone is selected from one or more of active polyether silicone, polydimethylsiloxane, polymethyl hydrogen-(dimethyl)siloxane, terminal hydroxyl polydimethylsiloxane and aminoethyl iminopropyl polysiloxane; Preferably, the aromatic hydrocarbon solvent contains one or more of o-xylene, m-xylene, p-xylene, 1,3,5-triaminobenzene, 1,2,4-triaminobenzene and 2,4-diaminotoluene.
10. The preparation method according to claim 5, characterized in that: The base film is selected from cellulose acetate film and / or polyamide film; the thickness of the base film is 0.01-0.1 mm.
Citation Information
Patent Citations
Seawater desalination membrane with strong acid and strong alkaline resistance as well as preparation method and application thereof
CN109304088A
Droplet interfaces
CA2889664C
Selective membrane having a high fouling resistance
CN101244367A
Polydimethylsiloxane / polyvinylidene fluoride composite film and preparation method thereof
CN104624062A
Method for preparing hydrophilic modified polyvinylidene fluoride membrane
CN104857866A
Cited By
High-selectivity composite diaphragm for seawater electrolysis hydrogen production and preparation method of high-selectivity composite diaphragm
CN120400927A